2013
DOI: 10.1002/humu.22280
|View full text |Cite
|
Sign up to set email alerts
|

DIPSTR : Highly Sensitive Markers for the Analysis of Unbalanced Genomic Mixtures

Abstract: Samples containing highly unbalanced DNA mixtures from two individuals commonly occur both in forensic mixed stains and in peripheral blood DNA microchimerism induced by pregnancy or following organ transplant. Because of PCR amplification bias, the genetic identification of a DNA that contributes trace amounts to a mixed sample represents a tremendous challenge. This means that standard genetic markers, namely microsatellites, also referred as short tandem repeats (STR), and single-nucleotide polymorphism (SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 47 publications
1
53
0
Order By: Relevance
“…To evaluate the discrimination power of DIP-STRs, the theoretical estimate of the DIP-STR informativeness (I) previously published [6] was used. This formula allows calculating the occurrence of informative genotypes based on the presence of DIP alleles unique to the minor DNA contributor, I = 2s 2 l 2 + 2s 3 l + 2sl 3 .…”
Section: Occurrence Of Informative Markers and Corresponding Discrimimentioning
confidence: 99%
See 2 more Smart Citations
“…To evaluate the discrimination power of DIP-STRs, the theoretical estimate of the DIP-STR informativeness (I) previously published [6] was used. This formula allows calculating the occurrence of informative genotypes based on the presence of DIP alleles unique to the minor DNA contributor, I = 2s 2 l 2 + 2s 3 l + 2sl 3 .…”
Section: Occurrence Of Informative Markers and Corresponding Discrimimentioning
confidence: 99%
“…1). We originally described an initial set of DIP-STRs to empirically validate the high sensitivity of the method in resolving unbalanced mixed samples [6][7][8]. This study showed that because of the allele-specific amplification, these markers are about 100 times more sensitive in detecting DNA mixtures than autosomal STRs currently used for DNA profiling.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The analysis of the sequence polymorphisms in repeat and flanking regions found at some loci has the potential to increase their discriminative power if appropriate techniques (e.g. DIP-STR typing, massively parallel sequencing) are applied [36,37]: the D6S2906 alleles *10-*16 consisted of two or three subgroups as defined by SNPs in their flanking regions. The more frequent alleles *10 and *12 (0.189 and 0.198, respectively) could be split up into allelic subgroups found in a 1:3:2 and 1:3 relation, respectively according to sequencing results.…”
Section: Discussionmentioning
confidence: 99%
“…When DNA profiling technique is being performed using any biological specimen from the individual, it promises the correct and unambiguous individualization, but in certain cases the forensic scientist may encounter the problem of mixed or completely mismatched DNA profile of a single individual [1,2]. STR's (short tandem repeat) may lead to erroneous conclusion when the source of the biological material being analyzed is from a person who is a genetic chimera.…”
mentioning
confidence: 99%